Gastrointestinal nematodes in goats in small holder flock around Gaborone, Botswana - Johansson, Tove (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2017)
Small ruminants are of great importance in developing countries, where people rely on them for meat, milk and hides. In Botswana, as well as in other African countries, a major health and production problem is internal parasites, such as nematodes. The control of nematodes has for many years relied solely upon anthelmintic treatment, which has led to emergence of resistant worms. This study was conducted to map gastrointestinal nematodes in goats around Gaborone in Botswana and to investigate their response to anthelmintic treatment with ivermectin. Ten farmers from three different areas around Gaborone were included, each of them keeping approximately 30 goats. A total of 10 animals from each flock were sampled, resulting in a sample size of 100 animals. Each animal was assessed in regards to body condition score (BCS) and color of conjunctivae (FAMACHA®), sampled for faecal material and blood and marked with spray paint. The whole flock was dewormed with ivermectin. Counting of nematode eggs in the faeces was done with a modified McMaster method, and HCT was done with microhematocrit tubes. Between 10-14 days after deworming, the farms were revisited and the animals that were positive the first time were resampled and new egg counts were performed. To assess the efficacy of ivermectin a faecal egg count reduction test (FECRT) was performed. Larval cultures from each positive flock were set and harvested larvae were used for DNA extraction and later PCR and gel electrophoresis to determine presence of Haemonchus contortus. The results showed presence of nematodes in all flocks, but with significant differences between all three areas. The lowest mean EPG was 30±42, and the highest 510±261. The top three highest mean EPG were observed in Kopong and the top three lowest mean EPG in Modipane. In Kopong, one flock had significantly higher faecal egg counts than all the other herds except from one in the same area. After deworming, only one flock (Modipane) was negative at the time of resampling while one flock in Kopong had higher egg counts than before treatment. Haemonchus contortus was shown to be present in 4 out of 10 flocks and in all three areas. Due to low levels of infection and sup-optimal doses of ivermectin, the results of FECRT and the assessment of anthelmintic resistance could not be considered valid. However, the complete lack of egg reduction in one of the flocks coupled with a management of frequent deworming strongly suggests presence of anthelmintic resistance to ivermectin in this particular flock.